Algorithmic design for customizable products with additive manufacturing - Fonseca, Rodrigo Rocha Lopes da (2021)
The constant development of computer technologies led to novel ways of designing products in order to adapt to an always changing industry and customer requirements. A contribution to this development is the greater of availability and quality of additive manufacturing technologies, which brought new possibilities of tailoring products to the customers needs, due to its digital nature, wide range of available materials, low cost, reduced production times and ability to manufacture geometries of increased complexity. Two approaches, parametric and generative design, have gained traction in recent years. They seek to assist in the design process, by assisting with alternative exploration, and tailoring products to certain specifications, utilizing computing power as a medium to assist in the decision making process. A third approach, algorithmic design, has received attention in recent years mostly in the field of architecture. It proposes utilizing scripts, either through a text or visual-based programming language as algorithms, to form a basis for inferring knowledge, interfacing with other tools and simplifying the process of product customization through customized user interfaces. In the present work, the concepts of parametric, generative and algorithmic design are reviewed in the light of engineering design, to ascertain the activities and processes which constitute them, as well as the relationship between them. With algorithmic design as the focus, the scripting capabilities of Autodesk’s Fusion360 are used to explore shape creation and the possibility of added customization through custom user interfaces, while also inferring knowledge from additive manufacturing and outlying the benefits of integrating such an approach inside a software tool’s ecosystem. A novel methodology is proposed to address a design problem using algorithmic design, by creating drone models based on user inputs through a user interface. The methodology focuses on simplifying design exploration for the early stages of a typical engineering design process, and prepares the model for the final shape creation by integrating other software tools, namely, Autodesk’s Generative Design. This work scratches only the surface of algorithmic design, and does not go into deterministic approaches as much as possible, as a way to demonstrate the possibilities it entails without being limited by specific approaches. Therefore, it serves as a basis for future works which seek to explore alternatives or optimize solutions using the methodology as a basis.